2011
DOI: 10.1111/j.1529-8817.2011.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

TESTING THE EFFECTS OF ELEVATED PCO2 ON COCCOLITHOPHORES (PRYMNESIOPHYCEAE): COMPARISON BETWEEN HAPLOID AND DIPLOID LIFE STAGES1

Abstract: The response of Emiliania huxleyi (Lohmann) W. W. Hay et H. Mohler, Calcidiscus leptoporus (G. Murray et V. H. Blackman) J. Schiller, and Syracosphaera pulchra Lohmann to elevated partial pressure of carbon dioxide (pCO2 ) was investigated in batch cultures. We reported on the response of both haploid and diploid life stages of these three species. Growth rate, cell size, particulate inorganic carbon (PIC), and particulate organic carbon (POC) of both life stages were measured at two different pCO2 (400 and 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 57 publications
2
47
1
1
Order By: Relevance
“…Mean exponential growth rates for C. braarudii at 15 • C were 0.68 d −1 . These values are well within the ranges reported in other studies carried out at similar temperatures for Calcidiscus (Langer et al, 2006;Buitenhuis et al, 2008;Fiorini et al, 2010Fiorini et al, , 2011Langer et al, 2012;Candelier et al, 2013;Müller et al, 2014) and H. carteri (Stoll et al, 2002;. Exponential growth rates of 0.4-0.5 d −1 signify that roughly half of the culture population undergoes cell division each day.…”
Section: Growth Ratessupporting
confidence: 75%
“…Mean exponential growth rates for C. braarudii at 15 • C were 0.68 d −1 . These values are well within the ranges reported in other studies carried out at similar temperatures for Calcidiscus (Langer et al, 2006;Buitenhuis et al, 2008;Fiorini et al, 2010Fiorini et al, , 2011Langer et al, 2012;Candelier et al, 2013;Müller et al, 2014) and H. carteri (Stoll et al, 2002;. Exponential growth rates of 0.4-0.5 d −1 signify that roughly half of the culture population undergoes cell division each day.…”
Section: Growth Ratessupporting
confidence: 75%
“…Von Dassow et al (2009) showed for Emiliania huxleyi that transcript levels of genes whose products are involved in coccolithogenesis (Ca 2+ , H + and HCO 3 − transporters) are expressed much more in the diploid (heterococcolith) than in the haploid (holococcolith) phase which has non-calcified coccoliths. The few studies concerning environmental effects on holococcoliths (Quintero-Torres et al 2007, Fiorini et al 2011a, Pedrotti et al 2012 will be discussed in the relevant sections.…”
Section: Heterococcoliths and Holococcolithsmentioning
confidence: 99%
“…There is no evidence of the effects of carbonate system chemistry on holococcolith-bearing haploid cells. This was examined by Fiorini et al (2011a) for Calcidiscus leptoporus and Syracosphera pulchra; however, the PIC of the haploid cells was below the detection limits. This may be of interest to pursue because holococcoliths persisted in the fossil record through variations in atmospheric and ocean chemistry (Medlin et al 2008).…”
Section: ↓(↑): Decrease (Increase);mentioning
confidence: 99%
“…Early experimental work with laboratory cultures and large-scale semi-enclosed field cultures, mesocosms, suggested that there was a clear reduction in calcification rates with increasing pCO 2 (Riebesell et al, 2000;Riebesell, 2004;Zondervan et al, 2002;Engel et al, 2005). They did, however, note that other effects such as growth rate and cell size changes could confuse this response, that the response was often muted (also shown by Fiorini et al, 2011) and that it was important to look at changes in the ratio of calcification to photosynthetic carbon fixation and at calcification rates per cell.…”
Section: Introductionmentioning
confidence: 99%